Public participation and climate change governance: Between political approach and local actors’ perspective in two Macaronesian territories - Mendonça, Ana; Leal Filho, Walter; Alves, Fátima (Frontiers in Environmental Science, 2023)
Climate Change (CC) is the major current environmental challenge, influencing the balance of ecosystems, livelihoods, social organization, public health, and well-being. The Autonomous Region of Madeira and the Autonomous Community of the Canary Islands considered outermost regions (ORs), form part of continental countries (Portugal and Spain, respectively), and integrate Macaronesia. Due to their location and idiosyncratic characteristics, they are also particularly vulnerable to CC. Regional and local mitigation and adaptation plans and strategies are in force, but policies still do not respond to the CC challenges or fully integrate public participation in their definition and implementation. This article investigates the relevance of public participation in CC policies, and how it has been carried out by decision-makers. Thereby, it intends to understand the evolution of CC policies in the archipelagos of Madeira and the Canary Islands, as they have met the interests of relevant scientific, administrative, and economic actors, often underestimating the contributions of other actors, and how public involvement and participation is key to resolve socio-environmental issues in the territories. With this aim in mind, we have conducted a document analysis of the legislation, programmes, and strategies on CC, complemented by twenty in-depth interviews, ten in Madeira and ten in Las Palmas of Gran Canaria, to a group of local stakeholders, among them scientists, technicians and politicians. Our study shows that despite the efforts levered by European and national guidelines, the status quo prevails, with political and institutional arenas systematically keeping their distance from concrete realities of quotidian life. The results show evidence that at international, supranational, and national levels, but also regional/local levels, CC policies often perpetuate domain ties, and sectoral and private interests, and are outlined according to narratives not accessible to all stakeholders. Therefore, discourses - political, academic, and corporate - prolong power relations and knowledge that express an institutionalized truth. Thus, we argue that proximity governance is crucial to raise awareness of socioenvironmental problems, complement existing knowledge, incite action, and empower local communities. This means that without a collaborative endeavour to boost the required changes, individually and collectively, CC policies might be difficult to implement.